PRONOMINA PERSONA DALAM ANTOLOGI CERPEN GONJONG 2: POTRET KELUARGA - Deswita, Isra; Agustina, Agustina; Juita, Novia (Jurnal Bahasa dan Sastra, 2018)
The purpose of this study is (1) describes the types of pronouns, (2) describes the categorization of pronouns with nouns, and (3) describes the nature of the reconciliation of pronouns in the short story anthology Gonjong 2: Family Portrait. The data of this research are sentences in which there is pronoun. The type and method used in this research is qualitative research with descriptive method. The source of this research data is the written source of the short story anthology Gonjong 2: Family Portrait. The data in this study were collected through the following steps: (1) reading all the short stories that are the source of the data, (2) mark the sentences in which there is pronouns, and (3) records to the data inventory format. Based on data analysis found three research results. First, found three types of pronouns, that is (1) the first single pronoun me, me, my-, me, me and your second pronouns we, us, (2) second single pronouns you, you, lu, you, you and the pronouns of both plural, you and (3) single third pronouns he, he, his, her and pronomina third plural they. Second, found two types of pronoun categorization relationships with nouns, that is (1) pronoun takrif me, me, me, you, you, you, you, you, he, he, his, his, they and (2) pronoun taktakrif who, respectively, and own. Third, two pronominal reference properties are found, that is (1) intrathexual pronouns and (2) extratectual pronouns.Keywords: pronouns, defined, not defined, intratextual, extratextual